2017
DOI: 10.1515/hukin-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Core Muscle Activation in Suspension Training Exercises

Abstract: A quantitative observational laboratory study was conducted to characterize and classify core training exercises executed in a suspension modality on the base of muscle activation. In a prospective single-group repeatedmeasures design, seventeen active male participants performed four suspension exercises typically associated with core training (roll-out, bodysaw, pike and knee-tuck

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 29 publications
(37 reference statements)
2
21
0
4
Order By: Relevance
“…Furthermore, the use of functional training can be very useful in endurance to reduce injuries, especially with extended performance times (Cugliari et al, 2017). In our study, the speed of the race correlates positively with the hours slept during the race itself, according with previous studies, observing a reduction in endurance performance following sleep deprivation (Oliver et al, 2009).…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, the use of functional training can be very useful in endurance to reduce injuries, especially with extended performance times (Cugliari et al, 2017). In our study, the speed of the race correlates positively with the hours slept during the race itself, according with previous studies, observing a reduction in endurance performance following sleep deprivation (Oliver et al, 2009).…”
Section: Discussionsupporting
confidence: 78%
“…Suspension training has become increasingly popular as a training tool [11]. In this activity the intensity of the exercise can be varied depending on the position of the body and the effects of gravity, with body weight acting as resistance.…”
Section: Introductionmentioning
confidence: 99%
“…TRX suspension training group in statistical data on the explosive force has significant progress (P<0.05), the apparatus resistance training group in the statistical data on the explosive force is no significant progress (P>0.05), on the statistical data only TRX suspension training group has significant progress, which conforms to the effects. such as 16 high school swimmers involved in 8 weeks of core training, the results show that the core training group in the explosive power project and the control group have significant differences [3]; The effect of the training of nuclear myocardium and the enhancement training on rugby players' special athletic performance found that core muscle group training can improve speed, explosive force, coordination and stability [4]. The effect of the 8-week core training on the students' vertical jumping and stability limit, the results show that the core training can improve the students' jumping performance [5].The effect of 8-week core training on the students' agility and jumping ability, the results show that the eight-week core training can improve the students' agility and jumping ability [6].…”
Section: Results and Analysismentioning
confidence: 96%